2014
DOI: 10.4103/0974-7761.148985
|View full text |Cite
|
Sign up to set email alerts
|

Perception of students and faculties regarding the formative assessment examinations in dental college in India

Abstract: Objectives: Student assessment is one of the vital elements in educational process. It is essential to conserve the formative nature of the assessment so that assessment is more structured and meaningful. Hence, it is necessary to review the existing formative assessment practises. The study was undertaken with purpose to estimate and compare the student and faculty perception about formative assessment examination in the institution. Materials and Methods: Seventy students and four faculties were enrolled for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Considering the wide variation in learners' study style, capabilities, compatibilities which might play as the crucial factors in their actual performance over time, a mixed model approach (as mentioned before) has been constructed for any possible categorization among the learners that could explain the variance in their performance score and further analysis of the pattern of the performance trajectory of these classes was carried out. [13] The result showed that a particular category (class 3) of students with relatively weaker performance recorded best trend in improvement in most of the formative tests, particularly for all the tests based on cognitive domain. This class had the largest number of the students and widest representation from different geographical distribution across the country with more male members.…”
Section: Discussionmentioning
confidence: 93%
“…Considering the wide variation in learners' study style, capabilities, compatibilities which might play as the crucial factors in their actual performance over time, a mixed model approach (as mentioned before) has been constructed for any possible categorization among the learners that could explain the variance in their performance score and further analysis of the pattern of the performance trajectory of these classes was carried out. [13] The result showed that a particular category (class 3) of students with relatively weaker performance recorded best trend in improvement in most of the formative tests, particularly for all the tests based on cognitive domain. This class had the largest number of the students and widest representation from different geographical distribution across the country with more male members.…”
Section: Discussionmentioning
confidence: 93%
“…Several improvements have been done by the teachers after conducting formative assessment; however, these were not done in various high quality activities. In contrast to the teacher"s lack of understanding of formative assessment, the result of the study conducted by and Panchbhai and Srivastava (2014) in Deemed University which took undergraduate students of dental faculty as the participants showed that 95.46% students agreed that formative assessment is needed to trigger them to study. Based on the result of Panchbhai and Srivastava" (2014) study, it shows that formative assessment is needed and so is the feedback given to the students by the teachers.…”
Section: Introductionmentioning
confidence: 92%
“…Some students' casual attitude toward formative assessment implies that they need to be more conscious of these intermediate assessments. The formative assessments make meaningful and successful academic development, thus they there is need for suggestions or criticism on an individual basis [5].…”
Section: Introductionmentioning
confidence: 99%